Simultaneous Monomialization (Contemporary Mathematics, 2020)
We give a proof of the simultaneous monomialization Theorem in zero characteristic for rings essentially of finite type over a field and for quasi-excellent rings. The methods develop the key elements theory that is a more subtle notion than the notion of key polynomials.
Keywords: valuations, monomialization, key polynomials